Creation of an innovation-friendly environment - Maceika, Augustinas; Šostak, Olga Regina (Business: Theory and Practice, 2014)
The paper focuses on identifying the methods useful for improving the process of creating an innovation friendly environment. For this purpose, conditions for innovation activity in industry were investigated, and the expert evaluation of the selected knowledge and the assessment of the importance of skills for the successful development of innovations were car ried out. The work referred to the analysis of the sources of scientific information, a sociological inquiry of the personnel of industrial enterprises, correlation analysis and expert evaluation. The study has found that for building the innovation friendly environment, knowledge of the psychology of creativity, personnel management, formation and implementation of the innova tion strategy, risk management, business development and sales organization are of a particular importance. Expert assessment has showed that abilities to work in a team, be an entrepreneur, use marketing tools, generate ideas and create new products play a crucial role in innovation development. A situation in industry companies has shown the currently existing various groups of employees with a different point of view on the surveyed parameter. Managers, workers, engineers and other staff have different opinions and knowledge, and therefore a well thoughtout policy is required for wider innovative activities. The directives of such a policy must be available for everyone.Inovacijoms palankios aplinkos kūrimasSantrauka Šio straipsnio tikslas – nustatyti būdus, kurie būtų naudingi inovacijoms palankios aplinkos kūrimo procesui pagerinti. Tuo tikslu buvo ištirtos inovacinės veiklos sąlygos pramonės įmonėse, atliktas atrinktų žinių ir gebėjimų svarbos sėkmingam inovacijų plėtojimui  ekspertinis  vertinimas.  Darbe  taikyti  metodai:  mokslinės  informacijos  šaltinių  analizė,  pramonės  įmonių  personalo  sociologinė  apklausa  ir  koreliacijos  analizė,  ekspertinis  vertinimas.  Tyrimo  metu  nustatyta,  kad  inovacijoms  palankios  aplinkos  kūrimui ypač svarbios kūrybos psichologijos, personalo vadybos, inovacijų strategijos formavimo ir įgyvendinimo, rizikos valdymo, verslo plėtros ir pardavimo organizavimo žinios. Ekspertinio vertinimo būdu nustatyta, kad darbo su kolektyvu, verslininkystės, pardavėjo priemonių naudojimo, idėjų generavimo ir naujų dalykų kūrimo gebėjimai yra taip pat labai svarbūs sėkmingai inovacijų plėtrai. Situacijos pramonės įmonėse tyrimai parodė, kad šiuo metu įvairiose darbuotojų grupėse yra prieštaringų tiriamų parametrų vertinimų. Vadovų, darbininkų, inžinierių ir kitų funkcijų darbuotojų nuomonės ir žinios skiriasi, todėl platesnei inovacinei veiklai plėtoti reikalinga gerai apgalvota politika, kurios direktyvos būtų visiems žinomos ir suvokiamos.Reikšminiai žodžiai: inovacijos, inovacijoms palanki aplinka, kūrybiškumas, verslumas, personalo vadyba.